Detecting cellular senescence in vivo: Imagining imaging better - Zachary M. Rabinowitz; Lina Cui (Aging and Cancer, 2023)
Abstract Methods to detect cellular senescence have become increasingly important, even more so in living animals and humans. This cellular state has been found to play fundamental roles in physiological processes as well as functioning detrimentally toward the advent or progression of pathological conditions. Importantly, the study of senescence involvement in these processes in vivo cannot be done without living‐friendly technologies enabling senescence detection. Furthermore, senotherapies or therapies that selectively kill senescent cells have emerged as a new therapeutic strategy for aging and age‐related diseases such as atherosclerosis, cancer, and neurodegenerative disorders and require tools to evaluate their use in vivo. As of now, our in vivo senescence detection toolkit includes genetically engineered reporter mouse models and small molecule imaging probes. Herein, we will focus on the detection of senescence in vivo, including a summary of its challenges, current detection methods and strategies, and a perspective on overcoming the current obstacles.